Problem Solving Analysis on Hots Problems in terms of Early Mathematical Ability - Yeni Heryani; Kartono Kartono; Kristina Wijayanti; Nuriana Rachmani Dewi (Universitas Negeri Semarang, 2022)
Abstract. The purpose of this study is to analyze problem-solving on HOTS problems in terms of early mathematical ability. This research method uses qualitative methods. The subjects in this study were students of class XI MIPA. The technique of determining the subject in this study began by grouping students into three groups of early mathematical abilities, namely high, medium and low. Then 3 students were taken as subjects, namely one subject for each group whose problem-solving steps met the problem-solving steps of Krulik & Rudnick. The data collection technique begins by grouping the categories of early mathematical abilities, giving math problem-solving tests and interviews on selected subjects to describe mathematical problem-solving and achievements on the HOTS indicator. Based on the results of math problem-solving tests and interviews on the subject, the results of this study showed that subjects with high early mathematical abilities were able to fulfill the read the problem step, explore step, select a strategy step, solve step and look back step so that the subject reached the indicator of analyzing, evaluating and create. Subjects with the medium category of initial mathematical ability were able to fulfill the read the problem step, the explore step, then select a strategy step, and the solve step, so the subject had not yet reached the creating indicator. Subjects with low mathematics initial ability category were only able to fulfill the read the problem step, the subject did not achieve all of the HOTS indicators.